Characteristics of Children with Non-Hodgkin Lymphoma Associated with Primary Immune Deficiency Diseases: Descriptions of Five Patients. (1st September 2013) - Emir, Suna; Vezir, Emine; Azkur, Dilek; Demir, Hacı Ahmet; Metin, Ayşe
<x xml:space="preserve">Abstract</x> Background: An increased incidence of non-Hodgkin lymphoma (NHL) has been seen in various primary immune deficiency (PID) cases. The present study aimed to evaluate the clinical characteristics and treatment outcomes of five cases with NHL associated with primary immunodeficiency. Methods: We retrospectively evaluated five patients with primary immunodeficiency who developed NHL. Two patients had ataxia-telangiectasia (A-T), one patient had common variable immunodeficiency (CVID), one patient had Bloom's Syndrome, and one patient had Wiskott-Aldrich syndrome (WAS). Results: All patients were male (median age, 8 years). Stage distribution was stage III in three patients and stage IV in two patients. Three patients had B-cell lymphoma and two had T-cell lymphoma. Reduced doses of Berlin–Frankfurt–Münster (BFM) and French Society of Pediatric Oncology (SFOP) regimens were used in four patients according to histopathological subtype. The two patients with ataxia and one patient with Bloom's Syndrome died of progressive/relapsed disease at months 5, 19, and 6, respectively. The patient with CVID associated with T-cell lymphoma has been in remission for 7 years. A full-dosage regimen of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) was successfully used in the patient with WAS and B-cell lymphoma; he was still in remission after 3 years. Conclusion: Primary immunodeficiency diseases are one of the strongest known risk factors for the development of NHL. Management of these patients remains problematic. There is a great need to develop new therapeutic approaches in this group. The use of rituximab in combination with CHOP may provide a promising treatment option for B-cell lymphomas associated with immunodeficiency.